Equity measures for the identification of public transport needs. Issue 3 (September 2020) - Gori, S.; Mannini, L.; Petrelli, M.
Highlights: The present paper deals with the identification of the PT needs. The proposed methodology takes into account equity issues of the PT services. The equity is measured through the "quality" of PT system. The proposed methodology has been applied in a real-size context of the city of Rome. In the case study the results show a changes of 7% of the GINI index. The results show the possibility of a significant increase in the modal split (+ 8%). Abstract: The present paper deals with the identification of the PT needs taking into account not only effectiveness and efficiency of the PT services but also equity issues. The PT needs refer to the identification of the possible spatial development of corridors, connecting areas of the urban agglomeration, in which there is the need of upgrading the overall performance of the PT services. The main novelties of the paper concern with the determination of the zones with a low "quality" of PT supply and the assessment of priorities and areas of upgrading of the PT system, so supporting the transport planning decisions. This paper focuses on measuring the equity in terms of "quality" of PT system using a new approach based on the computation of the GINI index and the Lorenz curve. In this context, the equity is related with the fair allocation of transport resources. The procedure proposed has been applied in a real-size context of the city of Rome. The case study shows promising results about the robustness of the proposed approach from the methodological point of view and the capability to assess effective measures in a real context. The results of the validation phase of the methodology and the results of the different phases of zone classification underline the strength of the choices made to represent the quality of public transport services and the GINI index approach. Specifically, taking into account the results by the point of view of equity, the GINI index shows a changes of about 7%, that is a promising result considering the few zones selected for the identification of public transport needs.